A case study on Manjalkaram (medicated alkaline lotion) in the management of Powthiram (fistula-in-ano) - Anpuchelvi, S.; Sritharan, G.; Ganesan, S. (Wolters Kluwer - Medknow, 2024)
Background: Abscesses around the lower rectum and anal canal are known as anorectal abscesses. These are crucial as they often culminate in fistula-in-ano. Anorectal abscess and fistulas are one of the most frequent results in the manifestation of simple or complex and extensive fistulous tracts. Karam (herbo-mineral preparation) therapy is a Siddha parasurgical technique commonly used to cure anal disease. Materials and Methods: Manjalkaram is a medicated alkaline lotion preparation that acts as herbal chemical cauterization agent to cure anal disease. A 60-year-old male patient, already treated with allopathy, experienced a recurrence of fistula-in-ano. The patient decided to get Siddha treatment and presented with the complaints of pain in the anal area, swelling, and discharge of pus with stool and mild irritation. The patient was diagnosed with fistula-in-ano. Purgatives were given the previous night to clean the bowel, and the following day, local cleaning was carried out by providing Triphala decoction as a herbal antiseptic lotion. A probe was inserted into the fistula, and a Manjalkaram-soaked medicated thread was inserted through the fistula and tied through an external opening to the internal opening with help of the probe. A Manjalkaram-soaked gauze (Manjalkaraseelai) was inserted and changed once in a week. Result: Even though fistula-in-ano is very difficult to treat, the patient got completely healed within 2 months with the effect of Manjalkaram application. Conclusion: Manjalkaram application is found to be an effective, time-saving, affordable, and acceptable treatment for fistula-in-ano.
Keywords: Fistula-in-ano; Manjalkaram; Siddha; Triphala decoction